2021
DOI: 10.1523/jneurosci.0921-21.2021
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Coding of Limb Kinematics in Motor Cortex across a Key Developmental Transition

Abstract: Primary motor cortex (M1) undergoes protracted development in mammals, functioning initially as a sensory structure. Throughout the first postnatal week in rats, M1 is strongly activated by self-generated forelimb movements-especially by the twitches that occur during active sleep. Here, we quantify the kinematic features of forelimb movements to reveal receptivefield properties of individual units within the forelimb region of M1. At postnatal day 8 (P8), nearly all units were strongly modulated by movement a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
63
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(73 citation statements)
references
References 59 publications
10
63
0
Order By: Relevance
“…Twitching during early-life REM episodes, therefore, could facilitate the transformation of uncoordinated movements during infancy to the fine-tuned sensorimotor maps of an adult. Sensory feedback from twitching limbs are thought to contribute to motor learning and sensorimotor integration (Blumberg et al, 2013 , 2020 ; Sokoloff et al, 2015 ; Rio-Bermudez and Blumberg, 2018 ; Glanz et al, 2021 ), as reafference from myoclonic twitches selectively activates brain regions such as the thalamus, cortex, hippocampus, and cerebellum in infant rats (Khazipov et al, 2004 ; Mohns and Blumberg, 2010 ; Tiriac et al, 2012 ; Sokoloff et al, 2015 ). Because reafference signals from self-movement are gated during waking, sleep disruptions that interfere with twitching, and their corresponding neuronal activity may disrupt sensorimotor maturation (Tiriac and Blumberg, 2016 ).…”
Section: Developmentmentioning
confidence: 99%
“…Twitching during early-life REM episodes, therefore, could facilitate the transformation of uncoordinated movements during infancy to the fine-tuned sensorimotor maps of an adult. Sensory feedback from twitching limbs are thought to contribute to motor learning and sensorimotor integration (Blumberg et al, 2013 , 2020 ; Sokoloff et al, 2015 ; Rio-Bermudez and Blumberg, 2018 ; Glanz et al, 2021 ), as reafference from myoclonic twitches selectively activates brain regions such as the thalamus, cortex, hippocampus, and cerebellum in infant rats (Khazipov et al, 2004 ; Mohns and Blumberg, 2010 ; Tiriac et al, 2012 ; Sokoloff et al, 2015 ). Because reafference signals from self-movement are gated during waking, sleep disruptions that interfere with twitching, and their corresponding neuronal activity may disrupt sensorimotor maturation (Tiriac and Blumberg, 2016 ).…”
Section: Developmentmentioning
confidence: 99%
“…Studies with kinematics coded with temporal basis functions have shown that a kinematic plan can be coded to reduce the bandwidth needed by a factor of ∼10 3 Hz (Iyer and Ballard, 2011;Won et al, 2020). More recently, sparse coding has been used to solve this problem (Glanz et al, 2021), despite unnecessary caution of its applicability to cortical motor areas (Beyeler et al, 2019). A tack that is still open would be our large sets of kinematic data to attempt to model cell responses 10 CMU Graphics Lab Motion Capture Database: http://mocap.cs.cmu.edu/ in cortical area M1 to see if they turn out to be correlated with Graziano's data.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Although the subplate receives functional neuromodulatory inputs already at early stages (Hanganu and Luhmann, 2004 ; Dupont et al, 2006 ; Hanganu et al, 2009 ), cortical layers 2 to 6 are only gradually innervated in an inside first—out side last sequence (Calarco and Robertson, 1995 ; Mechawar and Descarries, 2001 ). The emergence of the neuromodulatory inputs accompanies the developmental switch from bursting to continuous desynchronized activity (Colonnese et al, 2010 ) and the developmental changes in vigilance states and active movements (Mukherjee et al, 2017 ; Dooley et al, 2020 ; Glanz et al, 2021 ). Thus, these neuromodulatory systems have a progressively stronger influence on spontaneous and sensory evoked cortical function during the early postnatal period.…”
Section: The Challenges Of Studying the Neurophysiology Of The Developing Cerebral Cortex In Rodentsmentioning
confidence: 99%
“…Furthermore, spontaneous self-generated movements (myoclonic twitches) can be already observed very early and play an important role in the development of the sensorimotor system (Inacio et al, 2016 ; Dooley et al, 2020 ; Gomez et al, 2021 ). Head-fixation of newborn rodents allows simultaneous recordings of large-scale neuronal activity and spontaneous movements of the animal's snout including the whiskers, the forelimbs, hindlimbs, and the tail using electromyography (EMG) or multiple video camera monitoring (Dooley and Blumberg, 2018 ; Glanz et al, 2021 ; Gomez et al, 2021 ). Neuronal structures involved in the generation or modulation of spontaneous movements in newborns can be studied with imaging or multi-electrodes recording techniques.…”
Section: Neurophysiology Of the Developing Cerebral Cortex: What We Have Learnedmentioning
confidence: 99%
See 1 more Smart Citation